2017
DOI: 10.1016/j.aquaeng.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Pulse versus continuous peracetic acid applications: Effects on rainbow trout performance, biofilm formation and water quality

Abstract: a b s t r a c tPeracetic acid (PAA) products are being introduced to aquaculture as sustainable disinfectants. Two strategies are used to apply PAA: high dose pulse applications, or low dose continuous application. In the present study, their impacts on fish health and water quality were investigated in triplicate flowthrough tanks stocked with rainbow trout. The gentler and shorter water cortisol increase measured along twice-per-week pulse applications of 1 mg L −1 PAA indicated a progressive adaptation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 55 publications
2
28
1
Order By: Relevance
“…This strongly suggests that the decrease in the cortisol response after repeated exposure to PAA (Liu et al, 2017a(Liu et al, , 2017b) was a true process of habituation (Grissom and Bhatnagar, 2009) and was not the result of damage or disruption of the neuroendocrine cascade leading to the release of corticosteroids. This was further supported by the brain serotonergic activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This strongly suggests that the decrease in the cortisol response after repeated exposure to PAA (Liu et al, 2017a(Liu et al, , 2017b) was a true process of habituation (Grissom and Bhatnagar, 2009) and was not the result of damage or disruption of the neuroendocrine cascade leading to the release of corticosteroids. This was further supported by the brain serotonergic activity.…”
Section: Resultsmentioning
confidence: 99%
“…This protocol was maintained for 6 weeks, after which the exposure experiment was completed. At that time, the average mass of the fish was 190.6 g (SD = 29.9 g) with no differences among treatment groups (Liu et al, 2017b). .…”
Section: Fish Experimental Design and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, no significance difference was seen in the growth factors (i.e., feed conversion ratio (FCR), specific growth rate (SGR), body weight gain (BWG) and condition factor (CF)) between treated and control fish, while the survival rate in treated fish was significantly higher than control fish. Liu et al, [18] reported that the stress induced by the PAA-based product Aqua Oxides at high concentrations depends on fish species, being the growth of rainbow trout unaffected. …”
Section: Discussionmentioning
confidence: 99%
“…In aquaculture, there are two different strategies used to apply PAA products: pulse applications, short‐term treatments using high concentrations of PAA, up to several times per day with concentrations of 1–2 mg PAA/L or continuous applications of concentrations below 0.2 mg PAA/L (Liu, Straus, Pedersen, & Meinelt, 2017). In fish aquaculture systems, it could be shown that pulse application inhibits biofilm formation in the tanks, whereas continuous application of PAA promotes biofilm formation (Liu, Straus, et al, 2017). By pulse application therefore, the amount of bacteria in the system could be reduced and stable biofilms were prevented.…”
Section: Introductionmentioning
confidence: 99%